Referent Similarity and Nominal Syntax in Task-Based Language Teaching - Lambert, Craig; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume addresses an important gap in the literature on task design and second language use. Building on insights from over 50 years of research on the relationship between task demands and language use, it examines how referent similarity relates to developmentally-relevant variation in the use of nominal structures, comparative structures and abstract lexis among first and second language speakers of English. In addition to providing an empirical basis for future research on tasks, it shares both theoretical and practical information on task design, which will greatly benefit curriculum and material developers.
Chapter 1. Introduction -- Chapter 2. L2 Performance and Incidental SLA -- Chapter 3. Referential Communication and L2 Production -- Chapter 4. Tasks in L2 Syllabus Design -- Chapter 5. Referent Similarity -- Chapter 6. Referent Similarity and L2 Production -- Chapter 7. Methods -- Chapter 8. Results -- Chapter 9. Referent Similarity and TBLT -- References -- Appendix 1. Materials for the Study -- Appendix 2. Noun Phrase Coding Manual -- Appendix 3. Full Descriptive Statistics for NP Complexity.
Keywords: Language acquisition; Language and languages -- Style; Language and languages -- Study and teaching; Education -- Curricula; Language Acquisition and Development; Stylistics; Language Education; Curriculum Studies